2019
DOI: 10.1016/j.isci.2019.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium Secretion Induces Hepatocyte Lysosome Exocytosis and Promotes Parasite Entry

Abstract: The invasion of a suitable host hepatocyte by Plasmodium sporozoites is an essential step in malaria infection. We demonstrate that in infected hepatocytes, lysosomes are redistributed away from the nucleus, and surface exposure of lysosome-associated membrane protein 1 (LAMP1) is increased. Lysosome exocytosis in infected cells occurs independently of sporozoite traversal. Instead, a sporozoite-secreted factor is sufficient for the process. Knockdown of SNARE proteins involved in lysosome-plasma membrane fusi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In contrast, fusion of TVs with the host cell lysosomes may lead to their acidification, which in turn could activate PLP‐1 for sporozoite egress (Risco‐Castillo et al, 2015). The role of host cell lysosomes is probably more complex, as a recent study showed that P. yoelii sporozoites induce exocytosis of host cell lysosomes, which may promote parasite entry (Vijayan et al, 2019). In addition to pH, other mechanisms may regulate the activity of sporozoite PLP‐1, at the level of microneme secretion, membrane binding, or protein oligomerization for pore formation.…”
Section: The Role Of Environmental Sensing In the Switch Between Sporozoite Traversal And Invasion Modesmentioning
confidence: 99%
“…In contrast, fusion of TVs with the host cell lysosomes may lead to their acidification, which in turn could activate PLP‐1 for sporozoite egress (Risco‐Castillo et al, 2015). The role of host cell lysosomes is probably more complex, as a recent study showed that P. yoelii sporozoites induce exocytosis of host cell lysosomes, which may promote parasite entry (Vijayan et al, 2019). In addition to pH, other mechanisms may regulate the activity of sporozoite PLP‐1, at the level of microneme secretion, membrane binding, or protein oligomerization for pore formation.…”
Section: The Role Of Environmental Sensing In the Switch Between Sporozoite Traversal And Invasion Modesmentioning
confidence: 99%
“…Image z stacks were acquired with 0.2 µm steps and 25 - 27 images per stack. Images were deconvolved with a classic maximum likelihood estimation algorithm using Huygens software (Scientific Volume Imaging; The Netherlands) and experimentally determined point spread functions captured by imaging PS-Speck™ beads (Invitrogen) under experimental conditions, as done previously (Mast et al, 2018; Vijayan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…After hosts are infected with common parasitic protozoans such as Babesia, Plasmodium and Leishmania, lysosomes in host cells can engulf a large number of parasites [22][23][24]. Cathepsin D (CTSD) belongs to the aspartic protease family.…”
Section: Immune-related Proteinsmentioning
confidence: 99%